First evidence of murid gammaherpesvirus 4 (MHV-68) virus in the blood of oncological patients - Jozef Džubara; Iveta Štibrániová; Michaela Maliterná; Daria Romanivna Levina; Tomáš Žilka; Tomáš Žilka; Monika Baráthová; Petra Belvončíková; Jana Jakubíková; Peter Kabát; Peter Kabát (Acta Virologica)
Murid gammaherpesvirus 4 (prototype strain MHV-68) is a natural pathogen of murid rodents that is able to transform lymphocytes and induce lymphoproliferative diseases and tumor transformation in their host cells. Considering that this virus can infect and multiply in various human cell lines, we think it could also play an important role in the pathogenesis of some human types of cancer. We investigated and confirmed the presence of the replication and transcription activator rta (ORF 50) from MHV-68 virus in four peripheral blood samples from patients with lymphomas and gliomas.